2016
DOI: 10.1038/srep21434
|View full text |Cite
|
Sign up to set email alerts
|

High-energy X-ray focusing and applications to pair distribution function investigation of Pt and Au nanoparticles at high pressures

Abstract: We report development of micro-focusing optics for high-energy x-rays by combining a sagittally bent Laue crystal monchromator with Kirkpatrick-Baez (K–B) X-ray focusing mirrors. The optical system is able to provide a clean, high-flux X-ray beam suitable for pair distribution function (PDF) measurements at high pressure using a diamond anvil cell (DAC). A focused beam of moderate size (10–15 μm) has been achieved at energies of 66 and 81 keV. PDF data for nanocrystalline platinum (n-Pt) were collected at 12.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
(92 reference statements)
0
14
0
Order By: Relevance
“…The envelope function, f e ( r , d ), is defined as follows: Here, r is the atom–atom distance in Å, and d is the mean particle size in Å. H is a Heaviside step function which ensures that the envelope function goes to zero for r > d . This function has been successfully used to estimate the mean particle size as well as particle size distribution of nanosized particles using PDF. , Even though our samples contain particles at the micron scale, the envelope function gives us an estimate of the crystallite size for our gels. Hence, these data show that the C-(N)-A-S-H gel formed in AAS is predominantly amorphous as opposed to nanocrystalline, and the small amount of long-range ordering that is present is limited in intensity and distance (i.e., 25 Å).…”
Section: Resultsmentioning
confidence: 99%
“…The envelope function, f e ( r , d ), is defined as follows: Here, r is the atom–atom distance in Å, and d is the mean particle size in Å. H is a Heaviside step function which ensures that the envelope function goes to zero for r > d . This function has been successfully used to estimate the mean particle size as well as particle size distribution of nanosized particles using PDF. , Even though our samples contain particles at the micron scale, the envelope function gives us an estimate of the crystallite size for our gels. Hence, these data show that the C-(N)-A-S-H gel formed in AAS is predominantly amorphous as opposed to nanocrystalline, and the small amount of long-range ordering that is present is limited in intensity and distance (i.e., 25 Å).…”
Section: Resultsmentioning
confidence: 99%
“…A majority of NP species studied so far were found to be stiffer than bulk including but not limited to Au, Ag, Pt, TiO 2 , TiC, Fe 2 O 3 , CoFe 2 O 4 , CeO 2 , PbS, and BaF 2 . ,,,,, Nobel metal NPs are the common subjects in material research due to their ease of synthesis and ambient stability. As reported by Gu et al, high-pressure XRD measurements revealed a significantly higher B 0 of 290 GPa of 30 nm gold NPs over the bulk value of 170 GPa as well as a B 0 of silver increased noticeably from 116 to 140 GPa .…”
Section: Properties and Applications Of Nps Under Pressurementioning
confidence: 99%
“…It offers several advantages with respect to the use of energies in the range 10-30 keV. First, the enlarged range of Q range, where Q = (4πsinθ)/λ) is the scattering wave vector [116]. Second, the fast decay of the photoelectric cross-section with energy above the K-edge results in vanishing absorption corrections.…”
Section: Conclusion and Perspectivementioning
confidence: 99%